The endocrine disruptor bisphenol A may play a role in the aetiopathogenesis of polycystic ovary syndrome in adolescent girls. (3rd February 2015) - Akın, Leyla; Kendirci, Mustafa; Narin, Figen; Kurtoglu, Selim; Saraymen, Recep; Kondolot, Meda; Koçak, Selda; Elmalı, Ferhan
Abstract: Aim: Experimental in vitro studies have shown that bisphenol A affects steroidogenesis, folliculogenesis and ovarian morphology. The aim of this study was to investigate the role of the endocrine disruptor bisphenol A in the aetiopathogenesis of polycystic ovary syndrome (PCOS) in adolescents and its relationship with metabolic parameters, insulin resistance and obesity in this population. Methods: A total of 112 girls with PCOS and 61 controls between 13 and 19 years of age were enrolled in the study. Serum bisphenol A levels were measured by high‐pressure liquid chromatography. An oral glucose tolerance test was also performed. Results: Adolescents with PCOS had markedly increased serum bisphenol A levels (mean: 1.1 ng/mL 95% CI: 1.0–1.2) than controls (mean: 0.8 ng/mL 95% CI: 0.6–0.9, p = 0.001). When we compared the subgroups according to obesity, the main factor determining the significant increase in bisphenol A was the presence of PCOS, but not obesity (p = 0.029). Bisphenol A was significantly correlated with total testosterone (r = 0.52), free testosterone (r = 0.44), dehydroepiandrosterone sulphate (r = 0.37) and Ferriman–Gallwey score (r = 0.43) (p < 0.05). Conclusion: Adolescents with PCOS had higher serum bisphenol A levels than controls, independent of obesity. Bisphenol A concentrations were significantly correlated with androgen levels, leading us to consider that bisphenol A might play a role in the aetiopathogenesis of PCOS in adolescents.